Influence of Lauric acid on mechanical properties of Portland cement. Issue 1 (April 2021) - Sharma, Neha; Verma, Mohit; Sharma, Prashant
Abstract: In this research we focused on use of lauric acid as an admixture in cement. The main aim of this research is to scrutinize the outcomes of LA on different properties of cement i.e. normal consistency, setting time, compressive strength and the capillary absorption. As large amount of energy has been consumed during the grinding process of clinker therefore many researchers and investigators used fatty acids as a grinding aid to reduce this energy consumption. Herein, effect of LA as an admixture has been reported. Different proportion of LA i.e. 0.25%, 0.50%, 0.75%, 1.0%, 1.25%, 1.5%, 1.75%, 2.0% of dry weight of cement has been used as an admixture to know the properties of Portland cement. To test the compressive strength of Portland cement, total of 96 cubical specimens were prepared and tested for compression strength in UTM under curing stage of three, seven and twenty-eight days. Examined results showed that LA when used in appropriate amount extends the initial and final setting time of ordinary Portland cement. We noticed the decreasement in capillary absorption as amount of LA escalates. We have accomplished in upgrading the mechanical performance of cement, including the capillary absorption, the compressive strength and reducing the amount of mixing water used while modifying the setting time according to use requirements.